2003
DOI: 10.1002/jbm.a.10028
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale in vivo evaluation of the stiffness of Drosophila melanogaster integument during development

Abstract: A quasistatic nanoindentation technique, enhanced by scanning probe microscopy, was used to measure cuticle stiffness of live Drosophila melanogaster during its larval, pupal, and early adult development in vivo. Stiffness was defined as the reduced elastic modulus (E(r)), which is a material property related to the elastic modulus. E(r) was measured at the local contact while indenting the live sample at a constant loading rate using a spherical tip. E(r) was derived from the resultant force-displacement curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Residual deformation of the cuticle surface after indentation is similar to an elasticplastic contact, which is typical for most engineering materials (Bhushan and Li, 2003). The deviation of the residual imprint from the perfect pyramidal shape results from a visco-elastic relaxation, as is expected for soft biological materials (Wainright et al, 1976;Vincent, 1990;Kohane et al, 2003). This relaxation behaviour is especially evident on the lateral surfaces of the imprint, where the material almost goes back to its original condition ('cushion formation').…”
Section: Atomic Force Microscopymentioning
confidence: 80%
See 1 more Smart Citation
“…Residual deformation of the cuticle surface after indentation is similar to an elasticplastic contact, which is typical for most engineering materials (Bhushan and Li, 2003). The deviation of the residual imprint from the perfect pyramidal shape results from a visco-elastic relaxation, as is expected for soft biological materials (Wainright et al, 1976;Vincent, 1990;Kohane et al, 2003). This relaxation behaviour is especially evident on the lateral surfaces of the imprint, where the material almost goes back to its original condition ('cushion formation').…”
Section: Atomic Force Microscopymentioning
confidence: 80%
“…The results showed that the thickness of the cuticle and the development stage of the insect are important factors influencing cuticle stiffness (Kohane et al, 2003). The mean E r of 0.41·MPa, 15.43·MPa, and 4.37·MPa were determined by in vivo experiments for the cuticles of larvae, pupae and adult insects, respectively.…”
Section: Comparison With Other Insectsmentioning
confidence: 97%
“…Cuticular elasticity can also differ among body parts within a single species, as has been observed in the differing elasticity of the locust hind tibia, forewing and pleural cuticle (Jensen and Weisfogh, 1962). Cuticular stiffness may also vary across developmental stages as has been found in Drosophila among larvae, pupae, and adults (Kohane et al, 2003). These differences in material properties are attributable to factors such as sclerotization, the relative amounts of chitin and protein, and the types of matrix proteins making up the cuticle (Hillerton and Vincent, 1979;Kramer et al, 1995;Andersen et al, 1996).…”
Section: Materials and Structural Properties Of Insect Cuticle: Functimentioning
confidence: 98%
“…The application areas include microelectronics, optoelectronics, coatings for low-emission window glasses, and tribological coatings [22][23][24][25][26][27][28]. Presently, there is also a growing interest in probing biological materials [29][30][31][32][33][34][35] and food products [36,37]. Instrumented indentation measurements have also been used in the study of the deformation and fracture of rocks for a better understanding of rock mechanics related to geological evolution of the planets [38,39].…”
Section: Introductionmentioning
confidence: 99%